AIDS : prevention, information and education for health : criteria, examples and a model for a comprehensive national strategy directed at the general public and target groups : recommendations - Moerkerk, Hans (Strasbourg : Health Education Centre, 1987)
Fonds Suzan Daniel (FSD)
Engels
Brochure